Prompt Penetration and Substorm Effects Over Jicamarca During the September 2017 Geomagnetic Storm. Issue 8 (18th August 2021) - Fejer, B. G.; Navarro, L. A.; Sazykin, S.; Newheart, A.; Milla, M. A.; Condor, P.
Abstract: We used reanalyzed Jicamarca radar measurements to study the response of equatorial ionospheric electrodynamics and spread F during the main phase of the large September 2017 geomagnetic storm. Our observations near dusk on 7 September show very large upward drifts followed by a large short‐lived downward drift perturbation that completely suppressed the lower F region plasma irregularities and severely decreased the backscattered power from the higher altitude spread F. We suggest that this large short‐lived westward electric field perturbation is most likely of magnetospheric origin and is due to a sudden and very strong magnetic field reconfiguration. Later in the early night period, data indicate large, mostly upward, drift perturbations generally consistent with standard undershielding and overshielding electric field effects, but with amplitudes significantly larger than expected. Our analysis suggests that occurrence of storm‐time substorms is one of the major factors causing the large nighttime westward and eastward electric field perturbations observed at Jicamarca near the storm main phase. Our analysis also suggests that magnetospheric substorms play far more important roles on the electrodynamics of the equatorial nighttime ionosphere than has generally been thought. Key Points: Very strong changes on the vertical drifts and equatorial spread F intensity after dusk on September 7, 2017 Very large eastward and westward electric field perturbations from about 19 to 22 LT, likely enhanced by substorms Strong short‐lived response of equatorial spread F to a very large westward disturbance electric field at 19 LT